Reformasi Hukum Mengenai Penguatan Pelaksanaan Eksekusi Oleh Komisi Pengawasan Persaingan Usaha - Sara, Rineke; Pratama Sarwono, Aditya; Nandang, Asep; Samuel Wuisan, Ronald (JURNAL RETENTUM, 2023)
This study discusses the obstacles faced by the Business Competition Supervisory Commission (KPPU) in enforcing competition law, with a focus on the difficulty in obtaining adequate evidence, the lack of authority to force related parties, and the unclear procedures that can harm the reporter and the reported. The research method used is a normative legal approach with an analysis of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The main findings show that the KPPU faces serious obstacles in enforcing the law due to the lack of direct execution authority, non-transparent procedures, and the lack of legal protection for reporters. This study recommends several steps, including synchronizing Law No. 5 of 1999 with civil procedural law, granting direct execution authority to the KPPU, adding more stringent and effective sanctions, and increasing coordination between law enforcement agencies to accelerate the implementation of decisions and create a healthier and fairer business competition system.